Platelet Adhesion to Native Collagens Involves Proteoglycans and May Be a Two-Step Process - Behnke, O (Thrombosis and Haemostasis, 1987)
Adhesion of rat blood platelets to native rat tail collagen fibrils was studied in the electron microscope under conditions that preserved collagen-associated proteoglycans (CAPG). The CAPG molecules were aligned in chain-like configurations that encircled the fibrils with a 65 nm period; they appeared to coat the fibrils completely and extended 60-100 nm away from the fibril. The initial platelet-fibril contact occurred between the platelet glycocalyx and the CAPG of the fibrils i.e. between two surfaces with net-negative charges. When close contact was established between the fibril surface proper and the platelet membrane, CAPG were not identified in the area of contact, and the collagen-platelet distance was reduced to a ~10-12 nm wide gap traversed by delicate links in register with fibril periodicities.
Keywords: Platelets; Collagen; Proteoglycans